IMPORTANCE OF MILK PRODUCTION IN INCREASING OF COMPETETIVENESS OF SERBIAN AGRO-FOOD SECTOR - Lana Nastić; Jonel Subić; Jovanka Ninković (Ekonomika Poljoprivrede (1979), 2012)
Cattle production is the most present traditional branch of agriculture in Serbia, and special consideration was given to milk production as essential ingredient for the food security of the country. After World War II, since 1949 development of dairy industry in the former Yugoslavia began. From then on, in the field of milk production and processing many changes have occurred. However, due to accession to the European Union, in the following years this sector will go through significant changes because of harmonization with strict standards laid down in EU member states. Adoption of regulations and the compliance with the standards in the field of agriculture, agro food industry will get better quality raw material that will increase its competitiveness.